Attitudes toward fertility and fertility preservation in women with glioma. Issue 3 (26th September 2018) - Stiner, Rachel K; Clarke, Jennifer L; Sinha, Nikita; Chan, Jessica; Letourneau, Joseph M; Niemasik, Erin E; Rabbitt, Jane E; Chang, Susan M; Butowski, Nicholas A; Prados, Michael D; Rosen, Mitchell P
Abstract: Background: No studies have examined the fertility priorities of women undergoing treatment for their glioma. Glioma patients frequently undergo chemotherapy as part of their treatment; however, it is unknown whether patients truly are aware of its possible effects on their fertility. Our objective was to assess the fertility priorities of glioma patients and ascertain whether female glioma patients are being effectively counseled on the effects of chemotherapy on their fertility prior to beginning treatment. Methods: The sample was composed of female patients from the Neuro-oncology clinic of the University of California, San Francisco. Participants completed a cross-sectional survey between October 2010 and December 2013 exploring their attitudes toward fertility and their experience with fertility counseling prior to chemotherapy initiation. Results: Seventy-two women completed the survey. Analysis of the survey results showed that 30% of women receiving chemotherapy reported having a discussion regarding fertility preservation prior to beginning treatment. Of those who reported having this discussion, 80% were aware that chemotherapy could negatively affect their fertility. Many women reported that while fertility preservation was not important to them at the time of diagnosis, it was a priority for them at the time of survey completion. Although interest in having children tended to decrease after cancer treatment, the majority of respondents reported wanting a child after treatment. Conclusions: The data obtained in this study suggest a lack of understanding of reproductive priorities, which may be addressed with a more comprehensive fertility discussion prior to beginning treatment.